Gender, Nation, and Belonging: Representing Mothers and the Maternal in Asghar Farhadi’s A Separation - Shirazi, Mehra; Duncan, Patti; Freehling-Burton, Kryn (Atlantis, 2015)
In this article, we explore an understanding of gender and motherhood in Asghar Farhadi’s 2011 Oscar winning film, Jodayie Nader az Simin/A Separation, as a contested site where the discourses of gender and nation are constantly being negotiated. We suggest that the film’s unique cinematic language represents a significant contrast to stereotypical portrayals of motherhood in films. Also, by using transnational feminist cinema as a framework, we demonstrate the ways in which Farhadi engages with the relationship between gender and national belonging through a focus on borders, space, and place in contemporary Iran, offering a critique of both fundamentalist nationalist politics and neocolonial Western feminist assumptions.